2020
DOI: 10.1177/1012690220906389
|View full text |Cite
|
Sign up to set email alerts
|

Mid-life Chinese women’s understandings of sporting pain and injury: A non-Western cultural analysis via the Confucian concept of ‘ren’

Abstract: This study explored middle-aged Chinese female table tennis players’ experiences of pain and injuries in the context of life in a foreign country (New Zealand). Data were collected in two table tennis clubs via a year-long participant observation study and through life-story interviews. The Confucian concept of ren, which has similarities to new-materialist theorising, was drawn upon to frame our interpretations of the participants’ experiences of pain and injury. The concept encourages individuals who have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For example:
“Rose's reflections on her pain experiences underpinned her eventual self‐transformation so that she conscientiously changed her previously ‘arrogant and proud’ self to become more understanding and willing to share and help others. Thus, her experiences of pain worked to produce harmony…” 60
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example:
“Rose's reflections on her pain experiences underpinned her eventual self‐transformation so that she conscientiously changed her previously ‘arrogant and proud’ self to become more understanding and willing to share and help others. Thus, her experiences of pain worked to produce harmony…” 60
…”
Section: Resultsmentioning
confidence: 99%
“…For example: "Rose's reflections on her pain experiences underpinned her eventual selftransformation so that she conscientiously changed her previously 'arrogant and proud' self to become more understanding and willing to share and help others. Thus, her experiences of pain worked to produce harmony…" 60 Pain seemed to provide an opportunity to reflect on individual values and brought strength, understanding, and compassion. Some patients described a spiritual view and felt that the experience of pain brought them closer to God and led to spiritual purification.…”
Section: Pain Brings Strength and Spiritual Growthmentioning
confidence: 99%
“…The Christian faith was described as providing a framework through which pain could be understood and acknowledged in a positive sense. Past literature has also reported that chronic pain can be perceived as providing strength and spiritual growth 27–29 . Contemporary Sāmoan people often have a strong trust and faith in a transcendental being that is in control and can be sought for comfort and guidance 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Past literature has also reported that chronic pain can be perceived as providing strength and spiritual growth. [27][28][29] Contemporary S amoan people often have a strong trust and faith in a transcendental being that is in control and can be sought for comfort and guidance. 30 The Christian faith was presented by informants as enabling acceptance, solace and hope amid pain, and a lower reliance on medication or interventional treatment.…”
Section: Pain Is Interpreted Holisticallymentioning
confidence: 99%